Promoting Growth in Sub-Saharan Africa : Learning What Works - Ghura, Dhaneshwar (Economic Issues; Economic Issues ;, 2001)
Africa is the world's poorest continent, but amid all the bad news, there is hope for change. This pamphlet examines the lessons to be learned from some of the more successful economies south of the Sahara, and discusses a policy framework to promote sustainable economic growth and reduce poverty across the region.